Impact of shale gas on cointegration between natural gas and crude oil prices - Meriem BRAHIMI; Boubakeur BENLAIB (Journal of Excellence for Economics and Management Research, 2021)
Several recent studies establish that the prices of crude oil and natural gas are cointegrated. Yet sometimes in the past many voices have noted that the two sets of awards appear to have "decoupled".This article explores the cointegration relationship between the prices of natural gas (HH) and crude oil (WTI) in the United State, using econometric models (VAR, VECM) during the period from January 1997 to September 2020, which is experiencing several structural ruptures. The production of natural gas has recorded strong growth attributable to shale gas which depends more on liquid than on dry gas, the prices of which are strongly linked to the prices of crude oil, it is therefore possible to draw inspiration from the American experience in order to, to study the impact of shale gas for producing countries in general and Algeria in particular.